189k views
2 votes
Graph ​ g(x)=−2x2−12x−24 ​.

User LoLance
by
6.7k points

2 Answers

4 votes

Answer:

-3,-6 and -2,-8

Explanation:

took the test

User Kevin Chavez
by
6.1k points
2 votes

Answer:

See graph in attachment

Explanation:

We want to graph the function,


g(x)=-2x^2-12x-24


First, let us rewrite the function in the vertex form;


g(x)=-2(x^2+6x)-24



\Rightarrow g(x)=-2(x^2+6x+(3)^2)--2(-3)^2-24



\Rightarrow g(x)=-2(x^2+6x+(3)^2)+2(9)-24



\Rightarrow g(x)=-2(x+3)^2+18-24



\Rightarrow g(x)=-2(x+3)^2-6

The parabola opens downwards because
a=-2\:<\:0

The vertex of the parabola is
(-3,-6).


At y-intercept,
x=0.


This implies that,


g(0)=-2(0+3)^2-6=-18-6=-24


At x-intercept,
y=0

This implies that;


\Rightarrow 0=-2(x+3)^2-6


\Rightarrow -2(x+3)^2=6



\Rightarrow (x+3)^2=-3


This equation has no real number solutions because of
-3 on the right hand side. This implies that the graph has no x-intercepts.


We therefore draw a maximum graph through the vertex and the y-intercept to obtain the graph in the attachment.







Graph ​ g(x)=−2x2−12x−24 ​.-example-1
User Warren Chu
by
5.8k points